Ignition of hydraulic fluid sprays by open flames and hot surfaces - Liming Yuan (The National Institute for Occupational Safety and Health (NIOSH), 2006)
A study of the ignition of non-fire-resistant hydraulic fluid sprays was conducted by the National Institute for Occupational Safety and Health. Both an open flame and a hot steel surface were used as the external heat sources. With the open flame as the heat source, the minimum oil temperature and minimum spray nozzle pressure that resulted in an ignition were measured. The effects of the distance between the open flame and the nozzle and the nozzle orifice diameter on the ignitability of the hydraulic fluid sprays were examined. With the hot surface as the heat source, the minimum surface ignition temperature was determined. The degree of oil atomization and the relative direction of oil injection with respect to the hot surface are discussed. The ignition of oil sprays from the impingement of oil jets onto a vertical surface was also investigated. Finally, the results are compared with those obtained for fire-resistant hydraulic fluids. Keywords: Ignition; hot surface; open flame; hydraulic fluid